Synthesis of microporous polymers with exposed C60 surfaces by polyesterification of fullerenol. Issue 50 (6th June 2022) - Nishihara, Hirotomo; Harigaya, Akio; Castro-Muñiz, Alberto; Ohwada, Mao; Kyotani, Takashi; Nishina, Yuta
Abstract : Fullerene-based microporous polymers synthesized by polyesterification of fullerenol possess excellent stability against solvents and exposed C60 surfaces confirmed by enhanced hydrogen spillover. Abstract : Microporous polymers with exposed C60 surfaces have been synthesized by a new pathway of crosslinking fullerenol and terephthaloyl chloride or 1, 3, 5-benzenetricarbonyl trichloride via esterification. The resulting polymers are insoluble solids containing a large ratio of C60 with hydroxy groups and possess micropores with high specific surface area up to 657 m 2 g −1 . The microporous polymers thus obtained exhibit enhanced hydrogen spillover, which is a unique property of the C60 surface.